Pengaruh Keefektifan Pengendalian Internal, Komitmen Organisasi, Dan Asimetri Informasi Terhadap Kecenderungan Kecurangan Akuntansi - Ni Kadek Ari Erliani; Putu Nuniek Hutnaleontina (UNHI Press, 2023)
The purpose of this study is to determine the impact of internal control effectiveness, organizational commitment, and information asymmetries on the propensity for accounting fraud in the BUMDes of Bendadem District, Karangasem Province. The population for this study was all his BUMDes staff in the Bevandem District, with a total of 65 persons obtained through direct observation in the field. The sample size for this study was 65 individuals determined by nonprobability sampling techniques and tested using multiple linear regression analysis techniques. The results of this study show that the effectiveness of internal controls and organizational commitments have a significant negative impact on the propensity for accounting fraud. Information asymmetry has a positive impact on the propensity for accounting fraud. VillageOwned Enterprises (BUMDes) across the Bendadem District of the Karangasem Regency should be able to improve the internal control system within their organizations in the future so that they can increase their organizational commitment to avoid accounting fraud